2016
DOI: 10.1021/acssuschemeng.6b01339
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Depolymerization of Lignin Using a Novel Polyoxometalate-Protic Ionic Liquid System

Abstract: Oxidative depolymerization of lignin obtained from pine and willow can be achieved in a novel system encompassing the ionic liquid (IL) 1-butylimidazolium hydrogensulfate coupled with a vanadium based polyoxometalate (POM) under oxygen rich conditions. Along with an array of phenols and functionalized aromatics, vanillin and syringaldehyde were the main products extracted from the IL. The overall yield of aldehyde products were shown to be higher on lignin samples obtained with shorter pretreatment times, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 17 publications
1
64
0
Order By: Relevance
“…Yield (%) with respect to the loaded lignin ranged from 0.26 to 0.99 for Nb2O5 catalyst and from 0.41 to 0.90 for CoCl2 catalyst, respectively, under the tested conditions. The product yields obtained from this study were comparable with results from previous studies using vanadium-based POM in presence of IL 1-butylimidazolium hydrogen sulfate and H2O2 with a product (vanillin, syringaldehyde, and guaiacol) yield of 0.055% (De Gregorio et al, 2016;Prado et al, 2016a). Low product yield in this study may be due to repolymerization of depolymerized lignin and/or over-oxidization products to other intermediates which were not detected in the GC/MS.…”
Section: Possible Reaction Sequencesupporting
confidence: 83%
“…Yield (%) with respect to the loaded lignin ranged from 0.26 to 0.99 for Nb2O5 catalyst and from 0.41 to 0.90 for CoCl2 catalyst, respectively, under the tested conditions. The product yields obtained from this study were comparable with results from previous studies using vanadium-based POM in presence of IL 1-butylimidazolium hydrogen sulfate and H2O2 with a product (vanillin, syringaldehyde, and guaiacol) yield of 0.055% (De Gregorio et al, 2016;Prado et al, 2016a). Low product yield in this study may be due to repolymerization of depolymerized lignin and/or over-oxidization products to other intermediates which were not detected in the GC/MS.…”
Section: Possible Reaction Sequencesupporting
confidence: 83%
“…Recently ionic liquids (ILs) are extensively used for the conversion of cellulose, hemicellulose, and lignin into various value‐added chemicals . ILs have been employed as the solvent, additives, catalyst, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The yields obtained in our research were lower than those reported by other researchers. For example, De Gregorio et al [33] employed vanadium-based polyoxometalate as a catalyst in the presence of ionic liquid (IL) 1-butylimidazolium hydrogensulfate. The reported product yields for vanillin, syringaldehyde, and guaiacol were 0.055% with respect to lignin.…”
Section: Oyster Shell-supported Niobium Catalystmentioning
confidence: 99%